2004
DOI: 10.1002/adfm.200305149
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Origin of the 535 nm Emission Band in Oxidized Poly(9,9‐dioctylfluorene): The Essential Role of Inter‐Chain/Inter‐Segment Interactions

Abstract: We present a careful study of the effects of photo‐oxidation on the emissive properties of poly(9,9‐dioctylfluorene) (PFO) that addresses important issues raised by a recent flurry of publications concerning the degradation of blue light‐emitting, fluorene‐based homo‐ and copolymers. The photoluminescence (PL) spectra of thin PFO films oxidized at room temperature comprise two major components, namely a vibronically structured blue band and a green, structureless component, referred to hereafter as the ‘g‐band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
134
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(154 citation statements)
references
References 84 publications
(102 reference statements)
18
134
2
Order By: Relevance
“…[ 93 , 94 ] There are cases however where dissociation centres may be constituted by chemical sites such as oxidized polymer segments. [ 95 ] Some of these traps are likely to be present in every single study reported in literature since 100% material purity and oxygen free atmosphere are both very difficult to achieve. Their concentration however will differ from one study to another and so their infl uence on CPG.…”
Section: Why Early Charge Mobility Is Importantmentioning
confidence: 98%
“…[ 93 , 94 ] There are cases however where dissociation centres may be constituted by chemical sites such as oxidized polymer segments. [ 95 ] Some of these traps are likely to be present in every single study reported in literature since 100% material purity and oxygen free atmosphere are both very difficult to achieve. Their concentration however will differ from one study to another and so their infl uence on CPG.…”
Section: Why Early Charge Mobility Is Importantmentioning
confidence: 98%
“…1 Of all conjugated polymers, polyfluorenes, including poly-(9,9=-dioctylfluorene) (PFO), have attracted a special interest because of their efficient blue photoluminescence and one of the highest hole mobility values 2,3 (10 Ϫ3 to 10 Ϫ2 cm 2 /Vs) in combination with excellent chemical and thermal stability. 4,5 These features render PFOs with great application potential as blue-light-emitting diodes (LED), 6,7 optical switches, 8 thin film transistors, 9 solar cells, 6 and lasers. 10 A distinct structural feature, which is responsible for many unique physicochemical properties of fluorenes, is the presence of the bridging nonconjugated (sp 3 ) carbon atom between rigid planar biphenyl units ( Figure 1b).…”
mentioning
confidence: 99%
“…4 The tetrahedral character of the sp 3 -bonds of the bridging carbon allows for selforganization of PFO polymers into several distinct supramolecular structures at room temperature. 4 In films, PFO samples typically exhibit two morphological formations: amorphous glassy phase (␣ phase), in which PFO molecules have large torsional angles between the adjacent biphenyls, and the so-called ␤ phase with a high degree of organization and planar PFO molecules. 5,11,12 A strong variation of film morphology leads to a vast difference in photophysics of PFO materials.…”
mentioning
confidence: 99%
“…S2) can be fit with a bi-exponential function yielding time constants of ∼ 400 ps and 6.6 ns that are consistent with PFO exciton and fluorenone excimer respectively. [25] The radiative lifetime taken near the peak emission wavelength of the PFO (440 nm) also confirms the presence of efficient energy transfer from the PFO to the porphyrins. In fact, the lifetime of the pure PFO of about ∼ 400 ps is reduced upon loading with the MPP(Pt) and drops below the instrument detection limit ( ∼ 150 ps).…”
Section: Resultsmentioning
confidence: 62%